Eksperimen Pembelajaran Matematika dengan Strategi Discovery Learning dan Project Based Laerning Terhadap Hasil Belajar Matematika Ditinjau dari Tingkat Motivasi Belajar Siswa Kelas VIII Semester Genap SMP Negeri 1 Sambi Boyolali - Janita, Fanindya Dwi, Prof.Dr.Budi Murtiyasa, M.Kom (2017)
The purpose of this research is to analyze and test (1) to examine the influence of Discovery Learning and Project Based Learning strategies on mathematics learning outcomes (2) to examine the effect of learning motivation on students' mathematics learning outcomes. The influence of learning strategy interaction and motivation on mathematics learning outcomes of grade VIII students even semester SMP Negeri 1 Sambi. This type of research is experimental with quasi experimental design. This research takes two classes namely experiment class and control class. This research took place in SMP Negeri 1 Sambi Boyolali by taking class VIIIC as class as experiment class, and class VIII F as control class, experiment class or class VIII C treated with Discovery Learning strategy and control class or class VIII F treated with strategy Project Based Learning. The result of this research are (1) there is a significant influence between the use of learning strategy of Discovery Learning and Project Based Learning toward the learning result "based on the result of two way variance analysis with unequal cell (2) There is a significant influence of student's learning motivation toward mathematics learning result Based on the results of variance analysis and roads with unequal cells (3) There is an interaction between learning strategies and the level of learning motivation on mathematics learning outcomes